Strategi Komunikasi dalam Meningkatkan Produktivitas dan Kepuasan Kerja di PT. JNE Maumere, Kabupaten Sikka - Theresia Yunivita Ertilia; Veronika Toa; Vinsensius Alfarodino Keytimu; Yohanes Kristo Doke; Margareta Valencia Custodi (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2025)
This study aims to examine the internal communication strategies implemented by PT. JNE Maumere in enhancing employee productivity and job satisfaction. This research employs a qualitative descriptive approach, with data collected through interviews with the branch leader of PT. JNE Maumere. The findings indicate that the company implements an open communication strategy through daily briefings, monthly evaluations, and the use of various communication channels such as WhatsApp, Email, and Telegram. These communication strategies have proven effective in improving work efficiency, accelerating the resolution of operational issues, and increasing employee engagement and job satisfaction, particularly among staff and couriers. The main challenges in internal communication include extreme weather and geographical barriers that affect internet stability. However, PT. JNE Maumere views these challenges as opportunities for innovation, including plans to develop a dedicated internal communication application. Overall, open and well-structured communication strategies play a crucial role in supporting employee productivity and job satisfaction at PT. JNE Maumere.